2010
DOI: 10.1111/j.1365-2214.2010.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and management of epilepsy in secondary school pupils with and without special educational needs

Abstract: Epilepsy is more challenging to control in adolescents with special educational needs attending special schools. However, some pupils in mainstream secondary schools had poorly controlled epilepsy even when they did not have recognized special educational needs. Health and education professionals working across the range of secondary school environments need to be able to support pupils with challenging epilepsy, many of whom will also have special educational needs and some a physical disability, as an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Swiderska et al (2011) reported the epilepsy prevalence in a sample of children between ages 11 and 16 was 0.3 percent for children in mainstream education but 2.8 percent among children with special education needs. Moreover, seizures were considered well controlled in 78 percent of children without special education needs, while this was the case for only 41 percent of children with special education needs (Swiderska et al, 2011).…”
Section: Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Swiderska et al (2011) reported the epilepsy prevalence in a sample of children between ages 11 and 16 was 0.3 percent for children in mainstream education but 2.8 percent among children with special education needs. Moreover, seizures were considered well controlled in 78 percent of children without special education needs, while this was the case for only 41 percent of children with special education needs (Swiderska et al, 2011).…”
Section: Epilepsymentioning
confidence: 99%
“…Swiderska et al (2011) reported the epilepsy prevalence in a sample of children between ages 11 and 16 was 0.3 percent for children in mainstream education but 2.8 percent among children with special education needs. Moreover, seizures were considered well controlled in 78 percent of children without special education needs, while this was the case for only 41 percent of children with special education needs (Swiderska et al, 2011). Some authors suggest that the relationship between epilepsy and intellectual disability may be bidirectional: the prevalence of cognitive impairment among children with epilepsy is approximately 20-30 percent, with some studies reporting increases in IQ when surgery is performed to treat and prevent epileptic seizures (Chan et al, 2011).…”
Section: Epilepsymentioning
confidence: 99%
“…This study also suggested that an additional number of students without statements were recorded as needing "extra learning support" (Swiderske et al, 2011). Many children who develop epilepsy will have been identified as having special educational needs before the onset of epilepsy, suggesting that learning and behavioural problems precede the onset of epilepsy in a considerable proportion of children (Berg et al, 2005).…”
Section: Misdiagnosis In Epilepsymentioning
confidence: 77%
“…A study in the UK found that 35% of the students identified as having a diagnosis of epilepsy and attending secondary schools had a Statement of Special Educational Needs and the majority of those were attending special schools (Swiderske, Gondwe, Joseph, & Gibbs, 2011). This study also suggested that an additional number of students without statements were recorded as needing "extra learning support" (Swiderske et al, 2011).…”
Section: Misdiagnosis In Epilepsymentioning
confidence: 91%
“…A study published in 2010 also focused on the West Cheshire district but this time concentrated on the 62 students in the district with epilepsy who were attending secondary schools (Swiderske et al ., 2011). Twenty‐two (35%) of the students were identified as having a Statement of Special Educational Needs and, of these, 16 attended a special school and six attended a mainstream school.…”
Section: Epilepsy and Educational Provisionmentioning
confidence: 99%